Parotidite recorrente idiopática na criança - Vicente, Inês Nunes (2014)
Introduction: Recurrent idiopathic parotitis (RIP) is a frequent etiology of repeated inflammatory episodes of the parotid gland, in childhood. Objectives: To review current literature on the etiology, clinical presentation, diagnosis and treatment of RIP. Development: RIP is characterized by repeated episodes of swelling and pain in the parotid gland, usually accompanied by fever and malaise. Aetiology is multifactorial and, to date, unclear. Diagnosis is essentially clinical. Despite its benign character, recurrent parotitis can be a signal of other diseases, particularly in case of delayed onset of symptoms (from six-year-old) and bilateral involvement. The use of complementary tests should be individualized. Ultrasound is the diagnostic tool of choice and shows non-obstructive dilatation of glandular ducts (sialectasis). Treatment is mainly symptomatic. Prognosis is good with tendency to remission at puberty. Conclusions: RIP is a benign and self-limited condition. However, recurrent parotitis episodes should prompt investigation for underlying diseases, particularly in cases of late onset of symptoms (after age six years) and bilateral involvement.